Crystal structure of tetrakis(1,1,1,5,5,5-hexafluoroacetylacetonato)hafnium(IV) - Schwandt, W. Franklin (Acta Crystallogr E Crystallogr Commun, 2018)
The crystal structure of the title compound, [Hf(C(5)HF(6)O(2))(4)], has been determined. The asymmetric unit contains two Hf(hfac)(4) molecules (hfac = 1,1,1,5,5,5-hexafluoroacetylacetonate); both are located on general positions and have identical structures apart from the disorder involving three CF(3) groups in one of the two molecules. The molecules of Hf(hfac)(4) are arranged in layers that are parallel to the ab plane, and the coordination geometry of each hafnium(IV) center is a distorted square antiprism. An interesting aspect of the structure is that the hfac ligands are arranged so that the Hf(hfac)(4) molecules have idealized 2 point symmetry, in which two of the hfac groups bridge between the two squares. Although all other M(β-diketonate)(4) compounds of Hf (and Zr) also have square-antiprismatic geometries; in almost all of them the ligands are arranged so that the molecules have 222 point symmetry (in which none of the hfac ligands bridges between the two squares). The factors that favor one structure over another are not clear.